Living on the Edge : Vulnerability to Poverty and Public Transfers in Mexico - de la Fuente, Alejandro (World Bank Group, Washington, DC, 2015)
Social policy in Mexico has focused on identifying and supporting chronically poor households. Yet, Mexico has a significant number of households that are just above the poverty line who are not eligible, by definition, for antipoverty programs and are at risk of falling back into poverty in the event of an economic crisis or shocks like loss of employment and natural disasters. These shocks can have serious negative effects on welfare in the absence of social safety nets targeted to these households. This study uses household survey data to better understand these "vulnerable" households, including their profile and risk exposure and, more importantly, to document the extent to which these households are covered by public transfers and insurance mechanisms. The analysis shows that until 2010 most social programs, including the few with productive components, such as vocational training and productive investment grants, barely covered the vulnerable. The study concludes that public policies need to pay attention to the vulnerable households and find the right policy mix between targeted interventions and universal insurance schemes to serve this economic group.